Portable health clinic for sustainable care of mothers and newborns in rural Bangladesh. (August 2021) - Kikuchi, Kimiyo; Sato, Yoko; Izukura, Rieko; Nishikitani, Mariko; Kato, Kiyoko; Morokuma, Seiichi; Nessa, Meherun; Nohara, Yasunobu; Yokota, Fumihiko; Ahmed, Ashir; Islam-Maruf, Rafiqul; Nakashima, Naoki
Abstract: Background and objective: Regular health checkups are important for mothers and newborns to detect health problems at an early stage; however, this is often difficult in resource-limited settings. Therefore, the portable health clinic (PHC) for maternal and child health (MCH), a telemedicine health checkup system, was introduced as an intervention study in a rural area in Bangladesh. The aim of this research project was to report findings that we had observed at a mid-point of the intervention period. Methods: This was an intervention study conducted in Shariatpur, Bangladesh. The study population included pregnant/parturient women aged 15–49 years and their newborns. With the help of the newly created PHC for MCH, health workers, with a set of sensor devices in an attaché case, visited mothers and newborns at home to examine their health status. Their health status was triaged into four categories using a data management application, and in cases of affected or emergent health status, they were placed on remote video consultation with a doctor. Results: In total, 94 women were included in the PHC for MCH intervention. The rate of participants who received antenatal care at least four times or postnatal care at least once increased (from 29% to 51%, and from 27% to 78%, respectively) compared with before introducing PHC for MCH. Using the PHC for MCH, we detected health problems in pregnant/parturient women; a relatively high percentage had anemia (45–54%) and/or abnormal pulse rate (20–40%). Moreover, after introducing the PHC for MCH, more than 40% of women who received multiple antenatal care or postnatal care checkups improved their health status. Conclusions: The PHC for MCH could be an effective system to improve the health of mothers and newborns by increasing the availability of care. In the future, this system is expected to be used as a primary resource for maternity healthcare, not only in rural areas but also in other social environments.